Structured Early Follow-Up in Head and Neck Squamous Cell Carcinomas: A Retrospective Cohort Study - Philipp Dittmann; Bernhard Lehnert; Friedrich Ihler; Chia-Jung Busch; Markus Blaurock (Biomedicines)
Background/Objectives: The various head and neck squamous cell carcinoma (HNSCC) subtypes are among the most common cancers globally, with significant recurrence rates within the first two years post-treatment. Despite advancements in treatment, structured early follow-up remains crucial for timely diagnosis and effective salvage treatment. Methods: This retrospective study examines the impact of implementing a structured initial restaging between three and six months after the conclusion of initial treatment. The study population included 532 patients treated with curative intent at the University Medicine of Greifswald, Germany, between 2010 and 2019. Patients were divided into two groups: standard follow-up (SF) and adapted follow-up (AF). The AF group received standardized post-treatment restaging, including imaging and panendoscopy or PET-CT exams. Results: We found a trend towards earlier diagnosis and a reduction in recurrences, although these differences were not statistically significant. Secondary cancers were observed more frequently in the AF group, significantly affecting overall survival. Conclusions: Our cohort supports structured initial cancer follow-up in HNSCC. Although not significant, an initial multimodal exam after treatment was well tolerated and showed a trend toward earlier diagnosis.